Minimal Warnings, Positive Tones: How Social Media Content Normalizes E-Cigarette Use Among Indonesian Youth - Christian, Timotius; Alkadrie, Najwa Ulfa; Nikita, Gabriella (Jurnal Sosial Teknologi, 2025)
Indonesia is the country with the largest cigarette consumption in Southeast Asia and among the highest in the world. Cigarette consumption in the country is comparable to daily food expenditure, reflecting its widespread use. In addition to conventional cigarettes, e-cigarettes are also increasingly popular, especially among young people. The rise of social media has significantly increased exposure to e-cigarettes, as platforms allow user-generated content where anyone can create and share promotional materials. Unlike traditional cigarette advertising, which is regulated by specific broadcast hours, e-cigarette promotion on social media is largely unrestricted, leaving it up to content creators to self-regulate. Using a quantitative content analysis approach, this study examined 200 posts (100 from each platform) from June to September 2023. Content was categorized based on age and health warnings, promotional elements, and tone. Data reliability was ensured through inter-coder agreement. Findings show that both users and influencers largely portray e-cigarettes in a positive light, emphasizing their luxury and safety, while often ignoring age and health warnings. Marketing strategies such as freebies, product reviews, and vape tricks are increasingly appealing to young audiences. These findings highlight the urgent need for stricter regulation of e-cigarette promotion on social media to protect young people from potential health risks.